2023
DOI: 10.1155/2023/3720602
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potentially Functional Circular RNA/Long Noncoding RNA-MicroRNA-mRNA Regulatory Networks Associated with Vascular Injury in Type 2 Diabetes Mellitus by Integrated Microarray Analysis

Abstract: This research is aimed at figuring out the potential circular RNA (circRNA)/long noncoding RNA- (lncRNA-) microRNA- (miRNA-) mRNA regulatory networks associated with a vascular injury in type 2 diabetes mellitus (T2DM). Differentially expressed genes (DEGs) screened in T2DM-related expression datasets were intersected with genes associated with vascular injury in T2DM to obtain candidate DEGs, followed by the construction of an interaction network of DEGs. The upstream miRNAs of candidate genes were predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Previous studies have reported consistent expression of circRNAs in various human tissues and bodily fluids, including blood, saliva, and urine (5)(6)(7). circRNAs play an important role in regulating various biological processes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have reported consistent expression of circRNAs in various human tissues and bodily fluids, including blood, saliva, and urine (5)(6)(7). circRNAs play an important role in regulating various biological processes.…”
Section: Introductionmentioning
confidence: 94%
“…The transfection mixture was prepared by adding transfection reagents (Lipofectamine™ RNAiMAX) to the fresh culture medium along with either miRNA mimics or siRNAs targeting specific miRNAs (see sequences in Supplemental table 10). Different concentrations of mimics or siRNAs(1,5,10,20, 100 nM) were used. Cells that were not treated with miRNA mimic or were treated with negative control siRNAs were used as the control group, respectively.…”
mentioning
confidence: 99%